STRATEGI PEMASARAN BERBASIS DATA PELANGGAN UNTUK MENINGKATKAN LOYALITAS KONSUMEN - Joko Prasetiyo; Kamsidik Kamsidik (Yayasan Education and Social Center, 2026)
The increasing availability of customer data in the digital era has encouraged organizations to adopt data-driven marketing strategies to enhance consumer loyalty. This study aims to examine the effect of customer data–based marketing strategies on consumer loyalty, particularly in the context of Indonesian small and medium-sized enterprises (SMEs). A quantitative research approach was employed by distributing structured questionnaires to SME consumers, and the collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that data-driven marketing strategies have a significant positive impact on consumer loyalty, mediated by personalized marketing communication and perceived service quality. These findings highlight the importance of effective customer data management and analytics capabilities in improving customer retention and building sustainable competitive advantages. This study contributes to the marketing literature by providing empirical evidence on the role of customer data utilization in strengthening consumer loyalty within emerging market contexts.